Risk management of companies included in the EURO STOXX sustainability index: An investors' perception - Iulia Lupu; Ana Barbara Bobircă; Paul Gabriel Miclăuș; Tudor Ciumara (Amfiteatru Economic Journal, 2020)
Inclusion in the European Sustainability Index is a feature of companies that are perceived as "sustainable" in general. The objective of the research in this article is to analyse the perception of investors by investigating the extent to which these companies have lower risks than their peers (from the same industry). Consolidated risk measurement methodologies such as value at risk and expected shortfall have been used to conduct this research. We separated companies in the STOXX Europe 600 in two classes: firms that belong to EURO STOXX sustainability index and companies that belong only to the STOXX 600 index. Dynamic daily risk measures have been estimated for all these companies for the last decade (4 January 2010 - 3 March 2020), using data extracted from Bloomberg Professional platform. We show that the sustainable companies exhibit lower risks in the second part or our sample and that this phenomenon is irregular across sectors, but tends to be consistent inside a sector.
Keywords: G11; G15; G32; Q56; 330; companies' sustainability; risk management; stock indices; value at risk (VaR); expected shortfall